Exploring teachers’ views on the pedagogy of writing skills in English first additional language - Hlabisa, Samkelisiwe Ncane; Mhlongo, Hlengiwe Romualda; Govender, Samantha (Penerbit Universiti Kebangsaan Malaysia, 2023)
English writing proficiency in First Additional Language amongst Intermediate Phase learners has not reached satisfactory levels in South African schools. The aim of this paper was to explore teachers’ views on the teaching of writing skills in English First Additional Language specifically of grade 4 learners. The study sought to ascertain strategies used by teachers in teaching writing skills in selected EFAL grade 4 classrooms in uMkhanyakude District in the KwaZulu Natal province. A descriptive multiple case study design was adopted for this paper. Qualitative approach through semi-structured interviews and classroom observation were adopted, interpretive paradigm, purposive sampling, and thematic analysis were used. Findings revealed that teachers use various teaching strategies depending on the type of writing genre taught, needs of their learners, availability of resources and their context. Findings also indicated that teachers face challenges when teaching writing, they lack pedagogical knowledge to effectively teach writing and the support received is inadequate to enhance their pedagogy of writing skills especially for English First Additional Language. The paper concludes that there is a need for significant improvement on specific content and pedagogical knowledge that teachers possess to teach writing. Thus, this paper provides recommendations which emphasises the improvement of Initial Teacher Education in the writing domain by specifying the content and pedagogical knowledge to be taught, and ensuring adequate time dedicated to writing and writing instruction. Therefore, the paper advocates towards deep knowledge and understanding on how teachers can use a variety of strategies in trying to reinforce teaching of writing skills.